PERANCANGAN SISTEM INFORMASI MANAJEMEN EKSTRAKURIKULER BERBASIS WEB PADA SMA X JAKARTA - livia, samanta (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
Extracurriculars in education are intended to answer the demands of student’s needs. By participating in extracurricular activities, students will be assisted with creative learning patterns that can increase creativity. In fact, in limited school hours there are many activities that cannot always be carried out, so extracurriculars are created where the implementation is carried out outside school hours to accommodate students in meeting their needs, interests and talents. The management of the extracurricular information system at SMA X has problems, where students sometimes do not get information such as schedules, grades, extracurricular activities and extracurricular registration is done by submitting registration forms where this activity results in file accumulation, which is of course very ineffective nowadays. From the existing problems, the researchers created a web-based extracurricular management information system with HTML, PHP, Bootstrap and database programming languages. This system was tested using the usability testing method which was directly tested on extracurricular members. The method used in the development of the system is the waterfall method. This system is expected to facilitate the extracurricular information management process and can provide extensive information about the extracurricular activities themselves, so that the information provided is not broken down and integrated in one system and can be useful for students, teachers and schools.